Disentangling placebo effects in the treatment of migraine - Loder, Elizabeth W.; McGeeney, Brian (Nature reviews. Neurology, 2020)
A new meta-analysis of placebo-controlled trials of calcitonin gene-related peptide (CGRP) antibodies for migraine has shown that the direct biological effects of these treatments beyond the effects of placebo are modest, raising questions about how the ‘true value’ of these and other drugs are assessed.